2012
DOI: 10.1128/aac.01413-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hepatitis C Virus Inhibitors Targeting Different Aspects of Infection Using a Cell-Based Assay

Abstract: With 2 to 3% of the worldwide population chronically infected, hepatitis C virus (HCV) infection continues to be a major health care burden. Unfortunately, current interferon-based treatment options are not effective in all patients and are associated with significant side effects. Consequently, there is an ongoing need to identify and develop new anti-HCV therapies. Toward this goal, we previously developed a cell-based HCV infection assay for antiviral compound screening based on a low-multiplicity-of-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…One of the antihistamines, clemizole, was shown previously to have anti-HCV activity by interfering with the nonstructural protein 4B functions (21), but our screen indicated a much less potent activity of clemizole as compared to CCZ. The anti-HCV properties of cyclizines and phenothiazines have been reported previously and are consistent with our results (22)(23)(24)(25)(26). Compared to the phenothiazines in table S1, CCZ analogs were chosen for further studies on the basis of the following aspects: (i) higher potency and selectivity against HCV than phenothiazines, (ii) fewer CNSrelated side effects than phenothiazines, and (iii) potential for further structure modification to reduce side effects and increase anti-HCV activity.…”
Section: Discussionsupporting
confidence: 88%
“…One of the antihistamines, clemizole, was shown previously to have anti-HCV activity by interfering with the nonstructural protein 4B functions (21), but our screen indicated a much less potent activity of clemizole as compared to CCZ. The anti-HCV properties of cyclizines and phenothiazines have been reported previously and are consistent with our results (22)(23)(24)(25)(26). Compared to the phenothiazines in table S1, CCZ analogs were chosen for further studies on the basis of the following aspects: (i) higher potency and selectivity against HCV than phenothiazines, (ii) fewer CNSrelated side effects than phenothiazines, and (iii) potential for further structure modification to reduce side effects and increase anti-HCV activity.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, several groups have reported cell-based HCV infection systems for the screening of HCV inhibitors in various assay formats (12)(13)(14)(15). Traditionally, HTS was performed at a single fixed concentration of each candidate compound, which is prone to false positives and false negatives and requires extensive follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrated that reporter genes can be genetically engineered into certain locations of the HCV genome without impairing the viability of the virus (11). Several groups have reported cell-based HCV infection systems for the screening of HCV inhibitors in various assay formats (12)(13)(14)(15). Gastaminza et al developed a colorimetric assay measuring HCV E2 protein produced by HCVinfected cells in a 96-well plate format (12).…”
Section: H Epatitis C Virus (Hcv) Infection Affects Approximately 200mentioning
confidence: 99%
See 1 more Smart Citation
“…Reporter genes inserted into certain locations of the HCV genome could yield viable HCV capable of infection and replication in the cell culture (Koutsoudakis et al, 2006). In recent years, several groups have applied either wild-type HCV or modified HCV with reporter genes to develop cell-based HCV infection systems for the screening of HCV inhibitors (Chockalingam et al, 2010; Gastaminza et al, 2010; Kim et al, 2007; Wichroski et al, 2012; Yu et al, 2012). Cell-based HCV infection systems have the advantage of targeting various stages of HCV life cycle, thus significantly improving the efficiency of the drug screening process.…”
Section: Introductionmentioning
confidence: 99%